Medium wavelength infrared HgCdTe discrete photodetectors - Tsybrii, Z. F.; Andreeva, K. V.; Apatska, M. V.; Bunchuk, S. G.; Vuichyk, M. V.; Golenkov, O. G.; Dmytruk, N. V.; Zabudsky, V. V.; Lysiuk, I. O.; Svezhentsova, K. V.; Smolii, M. I.; Sizov, F. F. (Technology and design in electronic equipment, 2017)
The authors have developed the topology and technological fabrication route for discrete photodiodes (Θ = 0,5—1,5 mm) for the mid-wavelength infrared (MWIR) range, based on the mercury-cadmium-telluride (MCT) epitaxial layers. The paper describes technological processes of MCT photodiodes fabrication, including CdTe passivation layers growth, photolithographic processes for the formation of windows for B+ implantation, formation of metallic coatings, chemical surface treatments, cutting of the wafer on the discrete chips, assembling and bonding of the electrical contacts. Optical, photoelectrical and current-voltage characteristics of discrete MCT photodiodes for the spectral range of 3—5 microns are investigated in order to achieve the necessary operational parameters. FTIR transmission spectra were measured to evaluate samples quality and find the composition of x of Hg1–xCdxTe epitaxial layers grown by liquid phase epitaxy method. The limiting characteristics of photodiodes, which are determined by the magnitude of the detector current at the reverse bias and the product of the dynamic resistance at zero bias by the area of the photosensitive element R0Ad at the operating temperature of 77 K were discussed. The requirement for the parameter R0Ad was estimated for the operation of photodiodes of the mid wavelength infrared range in the BLIP (background limited performance) mode for the angles of view qi = 90° and qi = 30°: R0Ad ≥ 5·103 Ω·cm2. It was found from dynamical resistance characteristics that without bias in these MCT MWIR photodiodes R0Ad ≈ (0,57—1,08) Ω · 105 cm2 and these photodiodes can operate in BLIP mode.